Multi-user broadcast authentication scheme in wireless sensor networks with defending against DoS attacks - GUO Jiang-hong; MA Jian-feng (Tongxin xuebao)
A multi-user broadcast authentication scheme was proposed in wireless sensor networks with defending against DoS attacks（DDA-MBAS） based on vBNN-IBS signature,the bogus messages could be filtered using hash op-eration and user information.Compared with existing multi-user broadcast authentication schemes,except defending against node compromise attack and active attack,the bogus messages can be filtered with low energy consumption and the threat of DoS attack and collusion attack launched by compromised user can be limited effectively.